Investigations, actions and learning from an outbreak of SARS-CoV-2 infection among healthcare workers in the United Kingdom. Issue 4 (July 2021) - Saeed, Kordo; Pelosi, Emanuela; Mahobia, Nitin; White, Nicola; Labdon, Christopher; Ahmad-Saeed, Nusreen; Grieves, Ashley; Johnstone, Penelope; Higgs, David; Jeramiah, Sarah; Dailly, Sue; Henderson, Thelma; et al.
Background: We report an outbreak of SARS coronavirus-2 (SARS-CoV-2) infection among healthcare workers (HCW) in an NHS elective healthcare facility. Methodology: A narrative chronological account of events after declaring an outbreak of SARS-CoV-2 among HCWs. As part of the investigations, HCWs were offered testing during the outbreak. These were: (1) screening by real-time reverse transcriptase polymerase chain reaction (RT- PCR) to detect a current infection; and (2) serum samples to determine seroprevalence. Results: Over 180 HCWs were tested by real-time RT-PCR for SARS-CoV-2 infection. The rate of infection was 15.2% (23.7% for clinical or directly patient-facing HCWs vs. 4.8% in non-clinical non-patient-facing HCWs). Of the infected HCWs, 57% were asymptomatic. Seroprevalence (SARS-CoV-2 IgG) among HCWs was 13%. It was challenging to establish an exact source for the outbreak. The importance of education, training, social distancing and infection prevention practices were emphasised. Additionally, avoidance of unnecessary transfer of patients and minimising cross-site working for staff and early escalation were highlighted. Establishing mass and regular screening for HCWs are also crucial to enabling the best care for patients while maintaining the wellbeing of staff. Conclusion: To our knowledge, this is the first UK outbreak report among HCWs and we hope to have highlighted some key issues and learnings that can be considered by other NHS staff and HCWs globally when dealing with such a task in future.